Bach2: A Key Regulator in Th2-Related Immune Cells and Th2 Immune Response - Guo Liu; Feng Liu (Journal of Immunology Research)
Th2 immune response is essential for providing protection against pathogens and orchestrating humoral immunity. However, excessive Th2 immune response leads to the pathogenesis of Th2 inflammation diseases, including asthma, allergic rhinitis, and atopic dermatitis. Emerging evidence suggest a critical role of the transcription factor Bach2 in regulating Th2 immune responses. Bach2 serves as a super enhancer and transcriptional repressor to control the differentiation and maturation of Th2-related immune cells such as B cell lineages and T cell lineages. In B cells, Bach2 is required for every stage of B cell development and can delay the class switch recombination and antibody-producing plasma cell differentiation. In T cell lineages, Bach2 suppresses the CD4+ T cell differentiation into Th2 cells, restrains Th2 cytokine production, and promotes the generation and function of regulatory T (Treg) cells to balance the immune activity. Furthermore, studies in various animal models show that Bach2 knockout animals spontaneously develop Th2 inflammation in the airway and gastrointestinal tract. Genome-wide association studies have identified various susceptibility loci of Bach2 which are linked with Th2 inflammatory diseases such as asthma and inflammatory bowel disease. Here, we discuss the critical role of Bach2 involved in the Th2 immune response and associated inflammatory diseases.